The Worlds of Villard de Honnecourt: The Portfolio, Medieval Technology, and Gothic Monuments
1 online resource
Keywords: This book charts the past, present, and future of studies on medieval technology, art, and craft practices. Inspired by Villard’s enigmatic portfolio of artistic and engineering drawings, this collection explores the multiple facets of medieval building represented in this manuscript (Paris, Bibliothèque nationale de France, MS Fr 19093). The book’s eighteen essays and two introductions showcase traditional and emergent methods for the study of medieval craft, demonstrating how these diverse approaches collectively amplify our understanding about how medieval people built, engineered, and represented their world. Contributions range from the analysis of words and images in Villard’s portfolio, to the close analysis of masonry, technological marvels, and gothic architecture, pointing the way toward new avenues for future scholarship to explore. Contributors are: Mickey Abel, Carl F. Barnes Jr., Robert Bork, George Brooks, Michael T. Davis, Amy Gillette, Erik Gustafson, Maile S. Hutterer, John James, William Sayers, Ellen Shortell, Alice Isabella Sullivan, Richard Alfred Sundt, Sarah Thompson, Steven A. Walton, Maggie M. Williams, Kathleen Wilson Ruffo, and Nancy Wu.